A New Reading of Abortion in the Metropolis of Tehran: Based on the Lived Experiences of Women Born in the 1980s - Ghazanfari , Razieh Sadat (Health Nexus, 2025)
This study aims to examine abortion in the metropolis of Tehran using the grounded theory method, employing purposive and snowball sampling, and conducting semi-structured interviews with 17 women born in the 1980s who underwent at least one elective abortion in a clinic under the supervision of a specialist physician between 2021 and 2024. The data analysis, conducted using the interpretive analysis method of Strauss and Corbin, revealed two distinct pregnancy patterns among the respondents. In the first group, the causal factor was the convergence toward the discourse of definitive childlessness or low fertility. The contextual factors included the hardships of childbearing, economic difficulties, women's employment, and idealism in child-rearing. The intervening factors comprised a non-supportive environment for childbearing in society, marital life, and women's social networks. The interactions were characterized by changes in fertility behavior and a shift in women's perspective on childbearing. In the second group, the causal factor was the existence of extramarital relationships. The contextual factors included the dysfunctionality of marital life, prolonged suppression of sexual and emotional needs, husbands' extramarital affairs, and the perceived positive functions of extramarital relationships. The intervening factor was the obstacles to divorce. The interactions involved engagement with peer social networks, shifts in women's attitudinal and behavioral frameworks, and resistance to traditional and religious socialization. The core category derived from the study is "a new reading of abortion," which encompasses both the physical and non-physical consequences experienced by the actors involved.